2016
DOI: 10.1590/1413-70542016404007616
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of coffee zygotic embryos: dehydration and osmotic rehydration

Abstract: Conservation of plant genetic resources is important to prevent genetic erosion. Seed banks are the most common method of ex situ conservation; however, coffee seeds can not be stored by conventional methods. Cryopreservation is a viable alternative for long-term conservation of species that produce intermediate or recalcitrant seeds, as coffee. The aim of this work was to cryopreserve Coffea arabica L. cv Catuaí Vermelho IAC 144 zygotic embryos, and analyse the effects of dehydration prior cryopreservation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(15 reference statements)
0
7
0
1
Order By: Relevance
“…La regeneración de plántulas a partir de los embriones expuestos a las distintas etapas del protocolo (tratamientos) de crioconservación se puede observar en la Figura 4, dónde se muestra que el control mostró el crecimiento óptimo de plántulas (RP: 100 %), mientras que en el tratamiento con NL el crecimiento fue casi nulo (RP: 4 %), lo cual puede rela- prueba de TTC no son totalmente indicativos de la viabilidad final del tejido, ya que las enzimas encargadas de metabolizar el formazán pueden aún estar activas en células muertas (Nausch y Buyel, 2021), no obstante, este análisis puede ser de gran utilidad como primer acercamiento para discernir entre tejidos con potencial de germinación y regeneración. La prueba de viabilidad más confiable es sin duda la regeneración de los tejidos después del tratamiento (Pinto et al, 2016). Es importante destacar que la prueba de TTC se realizó inmediatamente después de cada uno de los tratamientos, en cambio, la regeneración de los embriones a plántulas se obtiene 15 d después de que el tejido es mantenido en cultivo de tejidos in vitro en medio de regeneración, por lo que en este periodo los embriones pudieron tener tiempo para poder recuperarse de alguna alteración debido a los tratamientos de crioconservación.…”
Section: Resultados Y Discusiónunclassified
“…La regeneración de plántulas a partir de los embriones expuestos a las distintas etapas del protocolo (tratamientos) de crioconservación se puede observar en la Figura 4, dónde se muestra que el control mostró el crecimiento óptimo de plántulas (RP: 100 %), mientras que en el tratamiento con NL el crecimiento fue casi nulo (RP: 4 %), lo cual puede rela- prueba de TTC no son totalmente indicativos de la viabilidad final del tejido, ya que las enzimas encargadas de metabolizar el formazán pueden aún estar activas en células muertas (Nausch y Buyel, 2021), no obstante, este análisis puede ser de gran utilidad como primer acercamiento para discernir entre tejidos con potencial de germinación y regeneración. La prueba de viabilidad más confiable es sin duda la regeneración de los tejidos después del tratamiento (Pinto et al, 2016). Es importante destacar que la prueba de TTC se realizó inmediatamente después de cada uno de los tratamientos, en cambio, la regeneración de los embriones a plántulas se obtiene 15 d después de que el tejido es mantenido en cultivo de tejidos in vitro en medio de regeneración, por lo que en este periodo los embriones pudieron tener tiempo para poder recuperarse de alguna alteración debido a los tratamientos de crioconservación.…”
Section: Resultados Y Discusiónunclassified
“…Recently, Coelho et al (2017) suggested that rapid drying to 20% moisture content (dry basis), followed by direct immersion in liquid nitrogen and later reheating in a water bath for 2 minutes allowed effective cryopreservation of coffee seeds. Pinto et al (2016) developed a protocol of cryopreserving coffee zygotic embryos using physical dehydration in silica gel, followed by osmotic rehydration after thawing. In another study, De Freitas et al (2016) demonstrated the successful cryopreservation and germination of zygotic embryos of Coffea arabica by immersing the zygotic embryos in plant vitrification solution.…”
Section: Evaluated Threementioning
confidence: 99%
“…So, for the successful of cryopreservation, it is essential that the plant material has been dehydration prior cryopreservation. A way to efficiently reduce the water content in the plant material is with the use of the silica gel dehydration that can be used for different material to physical desiccation (Pinto et al, 2016;Pérez-Rodríguez et al, 2017;Carmona-Martín et al, 2018). Since the silica gel technique is simple it becomes more reproducible.…”
Section: Dehydration Testmentioning
confidence: 99%